Awareness of female tourists on aspects of safety and security threats - Jabil Mapjabil; Christina Andin; Noorziah Mohd Salleh; Rosmiza M.Z; Mazdi Marzuki; Mohamad Pirdaus Yusoh; Jeannet Stephen; Datu Razali Datu Eranza; Nor-Ina Kanyo (Academic Inspired Network, 2021)
Studies on the security and safety assurance for tourists are not new, however, awareness regarding the safety of women tourists and the threat to their safety are still lacking. Therefore, the purpose of this article is to (i) identify the types and factors of security threats that concern women tourists when traveling in a city, and (ii) examine their awareness of safety issues when traveling in a city. In the context of this study, Kota Kinabalu is selected as the study location. A quantitative approach is used in this study through the distribution of questionnaires, interviews, and observations. A total of 93 respondents were included in this study. This study revealed that respondents were concerned about the threat of being robbed, which recorded 74.2%, followed by the threat of being kidnapped and raped, both of which recorded 44.1%. Moreover, there were two factors that may pose a threat to female tourists traveling within the city: 34.4% for location and 24.7% congestion in tourist areas. In terms of security, security officers were required in the city (4.22). Walking in tourist areas at night resulted in a mean of 2.58. In terms of safety awareness, the statement 'I am very concerned about my safety while traveling' received a 'very high' score, while the statement receiving a 'high' score was ‘I was scared when approached by a beggar while on holiday in Kota Kinabalu. As the result, the findings of this study have important implications for stakeholders involved in improving safety measures in Kota Kinabalu so that tourists, especially women, can enjoy the city's attractions.